Alterations in Water Status, Endogenous Abscisic Acid Content, and Expression of rab18 Gene during the Development of Freezing Tolerance in Arabidopsis thaliana. - Lang, V. (1994)
Treatments as diverse as exposure to low temperature (LT), exogenous abscisic acid (ABA), or drought resulted in a 4 to 5[deg]C increase in freezing tolerance of the annual herbaceous plant Arabidopsis thaliana. To correlate the increase in freezing tolerance with the physiological changes that occur in response to these treatments, we studied the alterations in water status, endogenous ABA levels, and accumulation of rab18 (V. Lang and E.T. Palva [1992] Plant Mol Biol 20: 951-962) mRNA. Exposure to LT and exogenous ABA caused only a minor decline in total water potential ([psi]w), in contrast to a dramatic decrease in [psi]w during drought stress. Similarly, the endogenous ABA levels were only slightly and transiently increased in LT-treated plants in contrast to a massive increase in ABA levels in drought-stressed plants. The expression of the ABA-responsive rab18 gene was low during the LT treatment but could be induced to high levels by exogenous ABA and drought stress. Taken together, these results suggest that the moderate increases in freezing tolerance of A. thaliana might be achieved by different mechanisms. However, ABA-deficient and ABA-insensitive mutants of A. thaliana have impaired freezing tolerance, suggesting that ABA is, at least indirectly, required for the development of full freezing tolerance.